Analisis Proses Desain Pembelajaran di SDI Baiturrachman Kota Tangerang - Magdalena, Ina; Septia, Nirmala; Heruni, Qulu Bunur (Lembaga Yasin AlSys, 2023)
In the process of teaching and learning activities a teacher must be able to manage the class well so that learning can be carried out in a conducive manner. In teaching each teacher has a method and uses different learning media that are adapted to the material to be explained. This research was conducted directly at SDI BAITURRACHMAN Kunciran Indah, Kec. Pinang, Tangerang City. Here we conduct research, namely to analyze how the learning design that occurs in high-grade students, namely grade 6. From the results of research that has been done, at SDI BAITURRACHMAN the learning design uses more lecture media and sometimes uses other media such as pictures, audio-visual, and others according to the material to be taught. In learning students do not only work individually, sometimes they will form a group to complete the task.